Analisa Hukum Pemisahan Peran Social Commerce terhadap Perlindungan Usaha Mikro Kecil dan Menengah - Rangga Aufar Rizan; Wiwik Sri Widiarty; Binoto Nadapdap (CV. Green Publisher Indonesia, 2026)
The development of globalization and the industrial revolution 4.0 has encouraged trade to switch to the digital realm through Social Commerce. However, this has a negative impact on offline MSMEs, so the government issued Trade Minister Regulation No. 31 of 2023 to limit Social Commerce as a promotional medium. However, this policy has not been effective because business actors such as TikTok Shop are still operating through partnerships with other e-commerce, so the goal of protecting MSMEs is not optimal. This research aims to discuss the alignment of the legal function of the issuance of the Minister of Trade Regulation in separating the role of Social Commerce with the objective of protecting Micro, Small, and Medium Enterprises, as well as to examine the efforts of the Government in providing protection to Micro, Small, and Medium Enterprises in the era of digital trade. The method of analysis is conducted in a normative juridical manner which involves the study of relevant regulations, by using the theory of legal protection, welfare state theory and people’s economy theory. Researcher finds that the regulation of role separation of Social Commerce has not been effective in protecting Micro, Small, and Medium Enterprises, because there are still loopholes that allow the practice of integrated Social Commerce to continue to operate through partnership schemes, so that the objective of the regulation is only formal and has not reflected the actual practice.